The continuity of hospital nursing care for Primary Health Care in Spain - Maria Fernanda Baeta Neves Alonso da Costa; Selma Regina de Andrade; Cilene Fernandes Soares; Esperanza I. Ballesteros Pérez; Sergio Capilla Tomás; Elizabeth Bernardino
ABSTRACT Objective: To learn the profile and activities carried out by the Hospital Nurse Liaison for the continuity of care in Primary Health Care in Spain. Method: An exploratory study with a qualitative approach developed in five University Hospitals in Madrid and three in Barcelona, with Hospital Nurse Liaisons who work in Hospitals in Madrid (8) and Barcelona (11). An online questionnaire was applied with open and closed questions for data collection. The data were analyzed by the content analysis technique in the thematic modality. Results: Nineteen (19) Hospital Nurse Liaisons participated in the study. The liaisons' ages ranged from 26 to 64 years old, the majority were women (94.73%) with experience between 21 and 30 years (52.63%), and had worked in this job between 6 months and 26 years. The Nurse Liasion is required to perform a clinical assessment of the patient prior to discharge and to contact the Nurse in the patient's area of origin by telephone or e-mail. It is necessary to have experience as an educator, to work in a team and have motivation. Conclusion: Nurses in Spain perform care continuity for Primary Health Care, in which their activities encompass the availability of resources and experience in managing the care of complex patients and their families.